Systemowe i operacyjne uwarunkowania rozwoju zastosowań technologii teleinformatycznych w działalności banków spółdzielczych - Kotliński, Grzegorz (System and Operational Conditions of Increasing Use of Tele-It Technologies in the Business of the Co-Operative Banks, 2005)
Co-operative banks are the financial institutions of special nature. Their most important feature is an extremely strong relation with the local population. Administration restructuring of the country has changed a lot as regards the above. Co-operative banks, despite difficulties, can take the opportunities that emerge. A proof of this is a gradual improvement of financial situation of the whole sector. Co-operative banks, as all banks do, face challenges resulting from the use of tele-It technology in operational business as well as the management of the financial institutions. In order not to disappoint their customers they have to be very careful and selective in choosing the proposed solutions keeping in mind their identity and trying to resist any danger associated with the new technologies. One of the biggest dangers that are always associated with IT novelties is the tendency to centralization that is hostile to the co-operative movement. Applications addressed to the co-operative banks must take into consideration their special requirements regarding internal architecture, module set and operational parameters.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1068, s. 99-113